Every kind of wicked - Black, Lisa, 1963- (Black, Lisa, 1963- Gardiner and Renner thriller., 2020)
Forensics expert Maggie Gardiner is swept up in a dangerous web of lies when detective Jack Renner's investigation into a university student's death violently converges with a suspicious overdose case being overseen by Maggie's homicide detective ex.